ENGLISH PRONUNCIATION IN GREAT BRITAIN - Akbarmirza Nurmatov; Abdulazizova Sevaraxon (Ustozlar uchun, 2025)
This article explores the diversity of English pronunciation in Great Britain, examining both traditional and evolving speech patterns. It discusses the historical role of Received Pronunciation (RP) as a standard accent and contrasts it with the rich variety of regional accents found across the country. The article highlights phonetic distinctions among different regions, including the north and south of England, Scotland, Wales, and urban areas like London. Additionally, it addresses the impact of social and cultural changes, such as media influence and multiculturalism, on contemporary pronunciation. The study of British pronunciation reflects not only linguistic evolution but also shifting attitudes toward identity and communication in modern society.